Carbon dioxide insufflation deflects airborne particles from an open surgical wound model. Issue 1 (January 2017) - Kokhanenko, P.; Papotti, G.; Cater, J.E.; Lynch, A.C.; van der Linden, J.A.; Spence, C.J.T.
Summary: Background: Surgical site infections remain a significant burden on healthcare systems and may benefit from new countermeasures. Aim: To assess the merits of open surgical wound CO2 insufflation via a gas diffuser to reduce airborne contamination, and to determine the distribution of CO2 in and over a wound. Methods: An experimental approach with engineers and clinical researchers was employed to measure the gas flow pattern and motion of airborne particles in a model of an open surgical wound in a simulated theatre setting. Laser-illuminated flow visualizations were performed and the degree of protection was quantified by collecting and characterizing particles deposited in and outside the wound cavity. Findings: The average number of particles entering the wound with a diameter of <5 μm was reduced 1000-fold with 10 L/min CO2 insufflation. Larger and heavier particles had a greater penetration potential and were reduced by a factor of 20. The degree of protection was found to be unaffected by exaggerated movements of hands in and out of the wound cavity. The steady-state CO2 concentration within the majority of the wound cavity was >95% and diminished rapidly above the wound to an atmospheric level (∼0%) at a height of 25 mm. Conclusion: Airborne particles were deflected from entering the wound by the CO2 in the cavity akin to a protective barrier. Insufflation of CO2 may be an effective means of reducing intraoperative infection rates in open surgeries.